Impact of Sagittal Talar Inclination on Total Ankle Replacement Failure. (August 2019) - Le, Vu; Escudero, Mario; Symes, Michael; Salat, Peter; Wing, Kevin; Younger, Alastair; Penner, Murray; Veljkovic, Andrea
Background: Restoration of ankle alignment is important in total ankle arthroplasty (TAA), but sagittal alignment of the talar component is less studied than coronal sagittal. Little has been published on the importance of sagittal talar alignment in TAA. The radiographic talar component inclination was hypothesized to be predictive of TAA survival, subsidence, and functional outcomes. Methods: A retrospective review of the Vancouver End-Stage Ankle Arthritis Database was performed on all TAAs at a single center over 11 years utilizing 1 of 2 implants. Talar component inclination (TCI) angles were measured and standard descriptive statistics were completed with a survival analysis. Inter- and intraobserver reliability were determined. Postoperative TCI angles were analyzed against several definitions of TAA survival and patient-reported outcome measures from the database. A total of 109 TAAs satisfied inclusion and exclusion criteria. Results: A postoperative talar component inclination angle greater than 22 degrees was associated with talar component anterior subsidence, defined as a change in that angle of 5 degrees or more between postoperative and last available radiographs. This was still significant after adjusting for confounders: age, gender, body mass index, and presence of inflammatory arthritis. All measured angles had good inter- and intraobserver reliability. Conclusion: Surgeons should avoid dorsiflexing the talar prosthesis during TAA, which hypothetically diminishes the ankle critical dorsiflexion range. This may cause anterior talar undercoverage in terminal dorsiflexion and may edge load the talar prosthesis, predisposing to anterior subsidence. Elevated TCI was a simple and reliable radiographic measurement to predict long-term TAA outcome due to predictable anterior subsidence of the talar prosthesis. Level of Evidence: Level III, retrospective comparative series.